Photosynthesis and growth of Amaranthus tricolor under strontium stress. (December 2022) - Cheng, Xuening; Chen, Can; Hu, Yuming; Guo, Xiliang; Wang, Jianlong
Abstract: Amaranthaceae are effective plants for cleaning soil contaminated by heavy metals and radionuclides. In this paper, Amaranthus tricolor was used to investigate the response of the plant photosynthesis to various concentration of strontium ions (0.2, 0.6, 3 and 6 mM), in order to determine the possibility of A. tricolor to remediate strontium contamination. The results showed that strontium ions (0.2–6 mM) had effect on light energy conversion and utilization in A. tricolor . Low level of strontium (0.2 mM) promoted the energy utilization in A. tricolor, while higher Sr concentration (3 mM or higher) increased the excess light energy in the plants. Under strontium stress of 6 mM, the acceptor side of PSII in A. tricolor leaves was more vulnerable to strontium stress than the donor side. Furthermore, strontium stress led to accumulation of QA − and block in QB downstream of the electron transfer chain in PSII of A. tricolor leaves. The tolerance ability of A. tricolor to strontium and remediation is also reflected in its biomass and strontium content in plants. Strontium at 3 mM or below promoted the growth of A. tricolor, while higher concentration inhibited the plant growth, but without obvious wilting or curling of leaves. The maximal dry weight increased by 36.29% in shoots, and 60.14% in roots when the spiked-strontium concentration reached 0.2 mM. The maximal strontium content achieved 8.75 mg/g dry wt in shoots, and 1.71 mg/g dry wt in roots respectively, when strontium concentration was 6 mM. Transfer factors (TFs: ratio of Sr content in shoots to that in roots) of strontium in A. tricolor ranged from 2.85 to 5.93, while bio-concentration factors (BCFs: ratio of Sr content in shoots to that in solutions) ranged from 22.57 to 49.66. In summary, A. tricolor showed the excellent potential to remediate strontium contamination. Graphical abstract: Image 1 Highlights: How to clean up the Sr-contaminated environment is of paramount importance. The response of A. tricolor to Sr 2+ stress in hydroponic solution was examined. The maximal Sr content in shoots and roots was 8.75 and 1.71 mg/g respectively. The TF and BCF ranged from 2.85 to 5.93, and 22.57 to 49.66, respectively. A. tricolor showed excellent potential to remediate strontium contamination.